Russian Lacquer Miniature in the Jewelry Production of the 1970s – 1980s: A Unique Artistic Innovation and the Problems of Its Implementation in Practice - Lavrov, Dmitrii E. (Actual Problems of Theory and History of Art, 2024)
Innovative tendencies were characteristic of Russian applied arts artists throughout the Soviet period. In particular, in the 1970s–1980s, the masters of Russian lacquer miniatures have carried out active experiments in jewelry. The most peculiar artistic experiment in the history of lacquer crafts of the late Soviet period attempted by the Union of Artists of the RSFSR was the creation of jewelry with Palekh lacquer miniatures. It constituted an important, albeit still little-known page in the history of the Palekh craft, which rarely attracted the attention of the researchers, none of whom had ever viewed this problem as a holistic phenomenon. The article discusses the course of these experiments in Palekh art, analyzes the reasons for their appearance and initial failures, as well as the impact that they had on the art of crafts related to Palekh: Fedoskino and Kholui. The article also analyzes the practice of turning to the jewelry business by Russian lacquer miniature artists of the post-Soviet period and present day. The main idea of the study is to substantiate the thesis that the long path traveled by the miniaturists of Palekh, Fedoskino, and Kholui in the 1970s–1980s turned out, despite some miscalculations, to be a generally fruitful creative experiment, which lessons should be used in the further artistic practice of Russian lacquer crafts.